Strengthening Emerging Sector of Indian Banking: - (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Strengthening financial systems has been one of the central issues facingemerging markets and developing economies.  This is because sound financial systems serve as an important channelfor achieving economic growth through the mobilization of financialsavings,  putting  them to productive use and transformingvarious risks (Beck,  Levin and Loayza1999;  King  and Levin 1993;  Rajan and Zingales 1998;  Demirgüç-Kunt, Asli  and  Maksimovic 1998;  Jayaratne  and Strahan  1996). Many countriesadopted a series of financial sector liberalization measures in the late 1980sand early 1990s that included interest rate liberalization, entryderegulations, reduction of reserve requirements and removal of creditallocation. In many cases, the timing of financial sector liberalizationcoincided with that of capital account liberalization. Domestic banks weregiven access to cheap loans from abroad and allocated those resources to domesticproduction sectors.